Pendataan Rumah Tidak Layak Huni (RTLH) Berbasis Survei Di Dusun Diwak Dan Karangtalun, Desa Karangkajen, Kabupaten Magelang - KKN Karangkajen (Fakultas Pertanian_Universitas Tidar, 2025)
The Thematic Community Service Program (KKN) conducted by Universitas Tidar students in Karangkajen Village, Magelang Regency, aimed to assist local governments in verifying and updating data related to uninhabitable houses (UH). The activity was carried out through a paper-based survey approach, where the team conducted direct field visits to households listed in the SIMPERUM (Housing Information System). During the visits, the students filled out UH assessment forms, conducted interviews with residents, observed the physical condition of the houses, and documented structural inadequacies through photos. This method allowed for more accurate and accountable data collection compared to relying solely on secondary information. The collected data was then uploaded to SIMPERUM and served as a reference for future housing improvement programs. This activity not only strengthened collaboration between universities and local governments but also empowered students to engage in community-based development practices.